Honest Character Development in Religion Based School (Study at SMP Imam Syafii Pekanbaru) - M.Khoiri (Jurnal Multidisiplin Madani, 2022)
This article examines the development of honest character in religion-based schools (study at Imam Syafii Junior High School). This article was written using a qualitative descriptive method to explain the development efforts honest character at Imam Syafii Junior High School Pekanbaru. Data collection techniques were carried out by means of observation, interviews and documentation studies. The data analysis technique of this research is by data collection, data reduction , and data presentation . The results of the study indicate that honest character building is carried out in the following ways : (1) Honest character development through a mentoring program. 2) The strategy of fostering honest character by taking responsibility for each other to build commitment among school members, (3) always implementing and carrying out the rules that have been set .